2019
DOI: 10.1038/s41598-019-42905-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between thyroid dysfunction and nephrotic syndrome: a clinicopathological study

Abstract: Abnormalities of thyroid function are common in patients with nephrotic syndrome (NS). However, a limited number of studies have reported on the association between clinicopathologic features and thyroid dysfunction in patients with NS. We retrospectively studied 317 patients who had been definitively diagnosed with NS. The NS patients with thyroid dysfunction showed higher urine protein, creatinine and lipid levels and lower albumin and hemoglobin than those with normal thyroid function, with no significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 21 publications
(20 reference statements)
1
36
2
3
Order By: Relevance
“…4 Li et al reviewed 317 patients with nephrotic syndrome and found that the most common renal pathology in patients with hypothyroidism was membranous nephropathy followed by minimal change disease. 5 While autoimmune pathways have been proposed as potential mechanisms underlying this association, so far, no precise antibody has been identified. 2,6 Interestingly, we did not find any autoimmune cause for profound hypothyroidism in our patient while he presented with secondary MN.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…4 Li et al reviewed 317 patients with nephrotic syndrome and found that the most common renal pathology in patients with hypothyroidism was membranous nephropathy followed by minimal change disease. 5 While autoimmune pathways have been proposed as potential mechanisms underlying this association, so far, no precise antibody has been identified. 2,6 Interestingly, we did not find any autoimmune cause for profound hypothyroidism in our patient while he presented with secondary MN.…”
Section: Discussionmentioning
confidence: 44%
“…Thyroid disease has previously been reported to have a link with development of glomerulonephritis . Li et al reviewed 317 patients with nephrotic syndrome and found that the most common renal pathology in patients with hypothyroidism was membranous nephropathy followed by minimal change disease . While autoimmune pathways have been proposed as potential mechanisms underlying this association, so far, no precise antibody has been identified .…”
Section: Discussionmentioning
confidence: 99%
“…Similar to PEW in CKD, nephrotic syndrome associated PEW is associated with an acceleration in atherosclerosis development, even in children [32]. Not only sarcopenia contributes to it, but also lipid disorders, increased activation of platelets, hypercoagulability, associated hormonal disorders, progressive renal failure [33][34][35][36][37]. Moreover, as we have discovered, hyperphosphatemia and hyperuricemia, recognized independent risk factors of cardiovascular events, were present in patients with severe NS [38][39][40].…”
Section: Discussionmentioning
confidence: 63%
“…The consequent proteinuria often precedes the reduction in GFR in hypothyroidism. Conversely patients with chronic kidney disease (CKD) and those with nephrotic syndrome are also known to present with hypothyroidism and/or subclinical hypothyroidism [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy individuals it has shown that 70% of the urinary proteins originate from the kidney and the urinary tract, whereas the remaining 30% represents proteins filtered by the glomerulus [4]. Being an ultrafiltrate of the plasma, the urine is less complex than plasma and a more appropriate biological fluid to study pathological processes arising from either the kidney, urogenital tract and even from systemic diseases [2,3]. This is also seen in cases of different systemic diseases in which proteolytic fragments generated from small circulating proteins peptides and vesicles pass through the glomerulus and change the urinary proteome.…”
Section: Introductionmentioning
confidence: 99%